Metamorphism and thermal history of the Jaljala Synclinorium, central west Nepal Himalaya (Journal of Nepal Geological Society, 1989)
Present mineralogical studies have revealed the thermal structure of metamorphosed pelitic and semipelitic rock terrains in the five different sections across the Jaljala Synclinorium in the central west Nepal Himalaya. The thermal gradient is estimated from the partitioning   of   Fe and Mg between the co-existing garnet and   biotite.  The  general   trend  of   the   thermal  structure   is  also  inferred  from  the  variation  of   the   Na/Na+ K   ratio  of   muscovite   in  different  sections.  The observed thermal structure and   the   metamorphism   of   the Jaljala Synclinorium is found to be explainable by a frictional shear heating model.